Variation of Tidal Range Based On Hijra Calendar And Its Relation With Ethno-Oceanography of The Sama Tribe In Eastern Indonesia - Salnuddin Salnuddin; I Wayan Nurjaya; Indra Jaya; Nyoman M.N Natih (Marine Science Department Diponegoro University, 2017)
Based on Ethno–Oceanography of the Sama tribe in Eastern Indonesia, they measured and determined tidal range when Sya’ban taking place. Why do they do so? The questions and objective of this study were intended to respond the scientific fundamental of Ethno-Oceanography of the Sama tribe. In order to achieve the objective of this study, the tidal range value in each Hijra month was compared and analyzed statistically (ANOVA). Tidal Analysis results showed that the tidal range at Sya’ban was higher and the deviation was lower than the other months. Moreover, ANOVA results showed that Sya’ban was significantly different (P<0.05) on Highest High Water Level (HHWL) throughout Hijra month. Keywords: Sama Tribe, Sya’ban, Hijra Calendar